Aggregate accounting earnings can explain most of security returns - Easton, Peter D; Harris, Trevor S; Ohlson, James A (Journal of Accounting and Economics, 1992)
The paper analyzes the contemporaneous association between market returns and earnings for long return intervals. The research design exploits two fundamental accounting attributes: (i) earnings aggregate over periods, and (ii) expanding the interval over which earnings are determined, is likely to reduce ‘measurement errors’ in (aggregate) earnings. These concepts lead to the level of (aggregate) earnings as a natural earnings variable for explaining security returns. We hypothesize that the longer the interval over which earnings are aggregated, the higher the cross-sectional correlation between earnings and returns. The empirical findings support this hypothesis.